Perceptions of the Cardiologists and Oncologists: Initial Step for Establishing Cardio-Oncology Service - Farhan, Hasan Ali; Yaseen, Israa Fadhil (Frontiers in Cardiovascular Medicine, 2021)
Background Over the last years there was no established cardio-oncology service in Iraq and no firm data about incidence of cardiovascular disease (CVD) among cancer patients. As initial step, we decided to conduct a national cardio-oncology online survey for cardiologists, oncologists, and their residents which would help us to understand the expected prevalence, problems, and readiness for collaboration between the two specialties. Objectives For evaluating the current national practice in the cardiology and oncology specialty fields and to identify the hidden gaps associated with the development or worsening of CVD among cancer patients. Methods An online survey including 19-question for cardiologist/cardiology residents (CCR) and 30-question for oncologists/oncology residents (OOR) about cardio-oncology service were sent to them including all Iraqi cities using google document form during December 2020. Results Total number of responses was 164, mainly from CCR (62.2%) while (37.8%) from OOR. Hypertension (HTN) was the main baseline risk factor (71%). A (77.5%) of CCR prescribe cardiovascular drugs versus (35.5%) by OOR. A (76.5%) of CCR and (79%) of OOR are facing difficulties in the management of cancer patients with established CVD. CVD was the leading cause for both hospitalization (30.7%) and mortality (48.4%). A (62.8) of CCR and (64.5%) of OOR have the interest to work in cardio-oncology service. Conclusions Based on cardiologists and oncologists’ perception, CVD is the main cause of hospitalization and mortality among cancer patients. High interest among CCR and OOR to work in cardio-oncology service. Positive initiatives are available to take the action plan in this emerging field.